Agresividad y socialización de los niños y niñas de cinco años en la institución educativa de nivel inicial jardín Nº 160 Mi Primer Aprendizaje Caballo Cocha 2022 - Yance Correa, Dania Veronica (2023)
The purpose of the study was to establish the relationship between aggressiveness and socialization of five-year-old boys and girls in the initial level educational institution No. 160 My First Learning. The sample consisted of 25 initial level students. The research was oriented by the quantitative approach of the basic type with a non-experimental and correlational design. The results showed that 48% of the students present a low and medium level of aggressiveness respectively, with respect to the socialization variable, the highest percentage 24% present a low level. Likewise, an inverse correlation was identified between aggressiveness and socialization. In conclusion, the Kendall-c Tau statistic (-0.619) showed that the aggressiveness and socialization variables have an inverse correlation (p value=0.000).